Exosomes and Exosome-Inspired Vesicles for Targeted Drug Delivery - Sophia G. Antimisiaris; Spyridon Mourtas; Antonia Marazioti (MDPI AG, 2018)
The similarities between exosomes and liposomes, together with the high organotropism of several types of exosomes, have recently prompted the development of engineered-exosomes or exosome-mimetics, which may be artificial (liposomal) or cell-derived vesicles, as advanced platforms for targeted drug delivery. Here, we provide the current state-of-the-art of using exosome or exosome-inspired systems for drug delivery. We review the various approaches investigated and the shortcomings of each approach. Finally the challenges which have been identified to date in this field are summarized.